Estudio de factibilidad para la creación de la cooperativa no financiera San Francisco, a través de la economía popular y solidaria para la inclusión laboral de los habitantes del sector de San Francisco de la parroquia Tarqui del cantón Guayaquil, provincia Guayas - Ortiz López, Mary Carmen (2016)
The study related to the feasibility study for the creation of non-financial Cooperative "San Francisco", through the Popular Solidarity Economy for the labor inclusion of people in the industry San Francisco, brings a systematic analysis of backing and support a community that is constantly with the need to supplement their economy everyday, there was a high number of unemployed, as well as people who despit having the know ledge and skills to do a job, is not related to a labor inclusion to enable them sustain the family economy and a chieve improvements based on established good I live in the present constitution. The basic objective of this researchis to establish parameters for sustained hoarding a data base of different activities and proceed to look for companies, institution sor homes where these services are required, so that in formation is spreading quality work and solvent demand forcraft activities in different sectors of the city of Guayaquil.……